2020
DOI: 10.32945/atr4225.2020
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Traits and Genetic Characterization of Native Chicken (Gallus gallus domesticus) in Selected Areas of Eastern and Western Samar, Philippines

Abstract: The Philippines has a number ofchicken genetic groups, mostly of non-descript and indigenous type. In view of the need to expand the information on native chicken diversity, this study was conducted to identify distinct qualitative traits and estimate genetic diversity and relationship among native chicken populations in selected areas of Eastern and Western Samar, Philippines. A total of 100 native chickens were qualitatively analyzed using a non-parametrictest, and 43 generated mtDNA sequences were used in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
1
0
1
Order By: Relevance
“…This finding was in line with Arlina et al (2015); Maharani et al (2018);and Tamsil et al (2020) that yellow and white or a mixture of these color were the dominant shank color found in Indonesia native chicken. Similar studies found that white and yellow were dominant in native chicken shanks in Bangladesh (Sharker et al, 2014), in South-Western Ethiopia (Bayou et al, 2022;Tadele et al, 2018), in Eastern and Western Samar of the Philippines (Godinez at al., 2020), and in transboundary area of Jammu and Kashmir in India (Singh et al, 2022).…”
Section: The Qualitative Traits Of "Bangkok" Chicken Offspringmentioning
confidence: 57%
“…This finding was in line with Arlina et al (2015); Maharani et al (2018);and Tamsil et al (2020) that yellow and white or a mixture of these color were the dominant shank color found in Indonesia native chicken. Similar studies found that white and yellow were dominant in native chicken shanks in Bangladesh (Sharker et al, 2014), in South-Western Ethiopia (Bayou et al, 2022;Tadele et al, 2018), in Eastern and Western Samar of the Philippines (Godinez at al., 2020), and in transboundary area of Jammu and Kashmir in India (Singh et al, 2022).…”
Section: The Qualitative Traits Of "Bangkok" Chicken Offspringmentioning
confidence: 57%
“…Upaya identifikasi, pendokumentasian, dan pemanfaatan ayam Kampung terutama informasi tentang karakteristik genetik fenotipik dan molekuler dari populasi ayam tersebut adalah sangat penting untuk pengambilan keputusan strategis mengenai konservasi dan/atau perbaikan mutu genetiknya (Boettcher et al, 2010). Data karakterisasi Ayam kampung secara fenotip maupun genotip masih dianggap penting untuk merancang konservasi ternak, pengembangan, dan program pemuliaan untuk pengelolaan genetik hewan sumber daya di tingkat lokal, nasional, regional, dan global (Godinez et al, 2020). Penelitian ini bertujuan untuk mengetahui frekuensi fenotipe dan genotipe sifat kualitatif ayam Kampung di Kecamatan Nusaniwe Kota Ambon.…”
Section: Pendahuluanunclassified